Geographic distribution of the Andean Lizard Liolaemus fitzgeraldi (Squamata, Liolaemidae) - Avila, Luciano Javier (2004)
Liolaemus fitzgeraldi Boulenger, 1899, is a small viviparous lizard (60–70mm snout–vent length [SVL]) that inhabits only high rocky valleys (over 2700m) of the central Andes of Argentina and Chile. All known populations are restricted to a small geographic area (Figure 1) but data are very scarce in nearby regions because access is very difficult, especially on the eastern side (Mendoza and San Juan provinces, Argentina). In the central Andes of Argentina it is the lizard with highest altitudinal distribution, reaching 4500m in some areas. Recently some data have been published about the species (Acosta et al., 2000; Avila and Soto, 1997), but the general geographic distribution is still poorly known. Here, I present information about geographic distribution, habitat and activity of Liolaemus fitzgeraldi.